TINGGALAN ARKEOLOGIS BENTENG BANGKUDU DI DESA KALIBU KECAMATAN KULISUSU - Yesrin Handayani (SANGIA JOURNAL OF ARCHAEOLOGY RESEARCH, 2017)
Fort Bangkudu was the first fortress in the kulisusu during the reign of La Ode ode which was the first king of the kulisusu kingdom in the seventeenth century. Seeing the condition of the building is not intactanymore, the purpose of this research is to find out and explain the remains contained in Fort Bangkudu andfind out the functions of Benteng Bangkudu. The problems of this thesis are; 1) what are the archaeologicalremains of the Bangkudu fortress, 2) what is the function of Bangkudu Fortress. This study also uses SpatialArcheology Theory and uses descriptive research methods to answer research problems. The results showedthat the archaeological remains found at Fort Bangkudu were 3 tombs, 2. Traditional houses, small huts,cannons and loose findings in the form of fragments of ceramics and pottery. As for the functions of BentengBangkudu, namely; First, the functions of Benteng Bangkudu in the past were: (1) as a center of defense andsecurity; and (2) As a place of settlement. Second, the function of Benteng Bangkudu at present is: (1) as thecultural center of the Kulisusu community; (2) as a Cultural Heritage object; and (3) as a place of historical andcultural attractions.